On a Two-Point Version of Transfinite Diameter - Buslaeva, S. F. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We study properties of a two-point version of the transfinite diameter of a set. By using relations obtained for its calculation, we prove a two-point version of the well-known Pólya theorem on an estimate from above for the Hankel determinants of a holomorphic function.